The effects of training conditions on athletes’ mental health throughout the COVID-19 pandemic: Psychometric validation of the Persian athlete psychological strain questionnaire - Hossein Azadi; Zohreh Meshkati; Simon Rice (Apunts Sports Medicine, 2024)
This study focuses on examining how different training conditions impact the mental well-being of athletes during the COVID-19 pandemic. It also aims to validate the Athlete Psychological Strain Questionnaire (APSQ) in the context of Iranian society. This descriptive survey was conducted on a population consisting of Iranian male and female sportspersons (16 to 40 years old), of whom 300 sportspersons were selected as the sample using snowball sampling. The tools used in this study were the APSQ, Kessler-10 Scale, and Ryff Mental Well-Being Scale, which were used online. SPSS 23 and AMOS 22 were used for data analysis. Confirmatory factor analysis (CFA) was utilized to assess the validity of the questionnaire, while the reliability of the questionnaire was examined through the application of Cronbach's alpha coefficient. Furthermore, Pearson's correlation test was employed to assess the concurrent validity of the questionnaire. Furthermore, discriminant analysis and ROC curve were utilized for examining the discriminant validity and cut-off point. Findings: Results indicate that sportspersons who had stopped playing sports during the COVID-19 pandemic suffered more psychological strain than those who continued playing sports during this period. The number of training sessions per week and the duration of each training session exhibited a significant inverse relationship with psychological strain. However, concern about progress and athletic burnout had a significant positive association with psychological strain. Furthermore, the validity and reliability of the APSQ were proved among Iranian athletes. Conclusion: The mental well-being of athletes is correlated with the extent of their training. The psychometric validation of the APSQ was confirmed in Iranian athletes. Therefore, researchers can use this scale to examine and detect early psychological strain and the psychological consequences of COVID-19 among these athletes. Early detection of psychological problems by this instrument may aid in improving athletes’ mental health.